PENGARUH KEPEMIMPINAN, MOTIVASI DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU AKUNTANSI SEKOLAH MENENGAH KEJURUAN DI KABUPATEN SERANG - Permatasari, Novelia Kiki (JURNAL RISET AKUNTANSI TIRTAYASA, 2019)
This study examines the influence of leadership, motivation, and emotional intelligence on the performance of accounting teachers. This study uses a vocational school located in serang regency as a research object. The number of samples in this study were 92 respondents. Data were analyzed using SEM (Structural Equation Model) method through the SmartPLS (Partial Least Square) version 1.0 program. The results of this study states that leadership has a significant effect on motivation. This means that leadership is needed and needs to be developed in improving employee work motivation and organizational effectiveness in achieving common goals. Emotional Intelligence has a significant effect on motivation. The higher the emotional intelligence that a teacher possesses the higher the motivation of his work. Leadership has a significant effect on the performance of accounting teachers. If leadership is applied appropriately, then the performance of accounting teachers is increasing. Emotional Intelligence significantly affects the performance of accounting teachers. The higher the emotional intelligence that an accounting teacher possesses, the better the performance will be. Motivation has a significant effect on performance. The higher the work motivation, the higher the level of performance that will be generated. For the vocational school is expected this research can be used as a means for evaluation and improvement of performance for the teacher. For further research is expected to add the external factor variable (environment, organizational culture, etc.) and add the respondent. Researchers can then consolidate research from other business entities, such as other sectors as well as test other factors or variables that may affect the performance of accounting teachers.